Legal Culture of Customary Inheritance Division in the Sasak Community: A Review from the Perspective of Legal Plurality and Islamic Legal Anthropology - Syibly, M. Roem; Walijah, Nurhasanah (Universitas Islam Indonesia, 2024)
This study aims to discuss the legal culture of inheritance distribution in a Sasak community in Jerowaru Village, Lombok by reveal the interaction of customary law and Islamic law used in distributing inheritance. This study is a qualitative descriptive which considers normative legal research and empirical legal research, as well as Islamic law anthropology and legal pluralism perspective. Qualitative data was collected by conducting in depth interviews with religious leaders, traditional leaders and community members. Number three: Sasak community has a pattern of heritage distribution (inheritance distribution) in the form of